Determining the Environmental Impacts of Extreme Hydrometeorological Events on Fire Management in the Guanacaste Conservation Area, Costa Rica - Pérez-Bertozzi, Laura (2024)
[Introduction]: The heightened levels of environmental degradation resulting from forest fires and their correlation with climate change are of global concern. In Costa Rica, hydrometeorological events categorized as extreme due to their significant impact, such as Hurricane Otto in 2016 and Tropical Storm Nate in 2017, appear to have induced changes in vegetation and, consequently, forest fuel. [Objective]: Therefore, this study analyzes the impact of extreme hydrometeorological events on the supply of vegetative fuel from 1997 to 2020 in the Platanares, El Avión, and Junquillal sites within the Guanacaste Conservation Area (ACG) in the northwest of the country. [Methodology]: The study utilized data from eight vegetation indices selected for their representation of forest growth.  Additionally, field verifications and information collection from official personnel and ACG volunteers were conducted to determine the effect of extreme events on the characteristics of vegetative fuel and its relationship with fire management and climate change adaptation. [Results]: The results obtained suggest that the vegetation in the investigated sites is in a state of natural regeneration but is increasingly exposed to the recurring influence of the ENSO phenomenon in its various phases (Neutral, La Niña, El Niño) and extreme hydrometeorological events, such as Hurricane Otto or Tropical Storm Nate [Conclusions]: These events could be contributing not to the quantity but to the intensity of forest fires.